Prenatal and Postnatal Expression of Glutathione Transferase ζ 1 in Human Liver and the Roles of Haplotype and Subject Age in Determining Activity with Dichloroacetate - Li, Wenjun; Gu, Yuan; James, Margaret O.; Hines, Ronald N.; Simpson, Pippa; Langaee, Taimour; Stacpoole, Peter W. (Drug metabolism and disposition, 2012)
Glutathione transferase ζ 1 (GSTZ1), also known as maleylacetoacetate isomerase, catalyzes the penultimate step of tyrosine catabolism and metabolizes several α-halocarboxylic acids, including dichloroacetic acid (DCA), an investigational drug used for lactic acidosis and, recently, solid tumors. Age-related differences have been suggested in DCA pharmacotoxicology, but no information is available on GSTZ1 ontogeny in humans. Here, we investigated the cytosolic GSTZ1 developmental expression pattern and the influence of haplotype on GSTZ1 activity with DCA by using human livers from donors between 10 weeks gestation and 74 years. GSTZ1 expression was very low in fetal livers (<2 pmol of GSTZ1/mg cytosol). The expression began to increase after birth in an age-dependent manner until age 7 years. GSTZ1 was then sustained at stable, yet variable, levels (median, 20.0 pmol/mg cytosol; range, 4.8–47.3 pmol/mg cytosol) until age 74 years. GSTZ1 activity with DCA was strongly associated with haplotype and expression level. Samples homozygous or heterozygous for GSTZ1A exhibited ∼3-fold higher DCA dechlorinating activity than samples carrying other alleles at a given level of expression. The correlations (r2) between activity and expression were 0.90 and 0.68, respectively, for GSTZ1A carriers (n = 11) and noncarriers (n = 61). GSTZ1 is expressed in mitochondria in addition to cytosol. The GSTZ1A allele exhibited similar effects in the mitochondrial fraction by conferring a higher activity with DCA. In summary, we report a neonatal onset and an age-related increase in GSTZ1 protein expression during human liver development. Haplotype influenced GSTZ1 activity with DCA but not protein expression.